Rút gọn các biểu thức: 3x(x – 2) – 5x(1 – x) – 8(x^2 – 3)

Câu hỏi :

Rút gọn các biểu thức: 3x(x – 2) – 5x(1 – x) – 8(x2 – 3)

* Đáp án

* Hướng dẫn giải

3x(x – 2) – 5x(1 – x) – 8(x2 – 3)

= 3x.x + 3x .( -2) – [5x.1 + 5x. (- x)] – [8x2 + 8.(- 3)]

= (3x2 – 6x) – (5x – 5x2) – (8x2 – 24)

= 3x2 – 6x – 5x + 5x2 – 8x2 + 24

= ( 3x2 +5x2 – 8x2)- ( 6x + 5x) + 24

= - 11x + 24

Câu hỏi trên thuộc đề trắc nghiệm dưới đây !

Giải Sách Bài Tập Toán 8 Tập 1 !!

Số câu hỏi: 794

Copyright © 2021 HOCTAP247